Carbene-supported triphosphorus anion - Yanbo Mei; Xue-Yi He; Jiancheng Li; Mo Liu; Qiuming Liang; Chengbo Yang; Liu Leo Liu (Nature Communications)
Abstract The stabilization of reactive anionic main group species utilizing carbenes constitutes a burgeoning and scarcely explored field. Herein, we report the synthesis of an anionic triphosphorus [P3]ˉ unit, supported by two cyclic (alkyl)(amino)carbenes (CAACs) in the form of potassium salts. This anion features a planar W-shaped conjugated C-P-P-P-C framework, characterized by 5-center-6-electron π delocalization and an additional σ lone pair located on each of the three phosphorus atoms. Remarkably, this anion is not only strongly basic and nucleophilic but also reductive, positioning versatile functionalization of the [P3] unit. This approach has advanced the isolation of unique carbene-supported cores, including [HP3], [P3N3R]−, [P3O]− and [P6], thus expanding the frontiers of phosphorus chemistry. Moreover, the addition of the two phosphorus fragments upon P-P bond cleavage of the [P3] unit to the triple bond of diphenylacetylene for the synthesis of an extended conjugated system was described.